Sisters in Spirit Christianity, Affect, and Community Building in East Africa, 1860-1970 - Prichard, Andreana C. (Michigan State University Press, 2017)
In this pioneering study, historian Andreana Prichard presents an intimate history of a single mission organization, the Universities' Mission to Central Africa (UMCA), told through the rich personal stories of a group of female African lay evangelists. Founded by British Anglican missionaries in the 1860s, the UMCA worked among refugees from the Indian Ocean slave trade on Zanzibar and among disparate communities on the adjacent Tanzanian mainland. Prichard illustrates how the mission's unique theology and the demographics of its adherents produced cohorts of African Christian women who, in the face of linguistic and cultural dissimilarity, used the daily performance of a certain set of "civilized" Christian values and affective relationships to evangelize to new inquirers. The UMCA's "sisters in spirit" ultimately forged a united spiritual community that spanned discontiguous mission stations across Tanzania and Zanzibar, incorporated diverse ethnolinguistic communities, and transcended generations. Focusing on the emotional and personal dimensions of their lives and on the relationships of affective spirituality that grew up among them, Prichard tells stories that are vital to our understanding of Tanzanian history, the history of religion and Christian missions in Africa, the development of cultural nationalisms, and the intellectual histories of African women.